Occurrence of Penicillium brocae and Penicillium citreonigrum, which Produce a Mutagenic Metabolite and a Mycotoxin Citreoviridin, Respectively, in Selected Commercially Available Rice Grains in Thailand - Shiratori, Nozomi (Toxins (Basel), 2017)
Commercially available rice grains in Thailand were examined to isolate the monoverticillate Penicillium species responsible for toxic yellowed rice. Penicillium species were obtained from seven out of 10 rice samples tested. Among them, one Penicillium citreonigrum isolate and six Penicillium brocae isolates were morphologically identified. The P. citreonigrum isolate produced the mycotoxin citreoviridin on a yeast extract sucrose broth medium. Mycotoxin surveys showed that citreoviridin was not detected in any samples, but one out of 10 rice samples tested was positive for aflatoxin B(1) at a level of 5.9 μg/kg. An Ames test revealed that methanol extracts from rice grains inoculated with selected P. brocae isolates were positive for strains TA100 and YG7108 of Salmonella typhimurium, suggesting the presence of base-pair substitution and DNA alkylation mutagens. Our data obtained here demonstrated that aflatoxin B(1) and toxic P. citreonigrum were present on domestic rice grains in Thailand, although limited samples were tested. Penicillium brocae, which may produce mutagenic metabolites, was isolated for the first time from the surface of Thai rice grains.